Anaerobic digestion of hydrothermal liquefaction wastewater from spent coffee grounds - Dias, M. E.; Oliveira, G. H.D.; Couto, P. T.; Dussán, K. J. [UNESP]; Zaiat, M.; Ribeiro, R.; Stablein, M. J.; Watson, J. T.; Zhang, Y.; Tommaso, G. (Elsevier, 2021)
Spent coffee grounds (SCG) are high water content lignocellulosic residues generated in large amounts by the instant coffee production industry. Recent interest in the use of SCG as biomass for biocrude oil production via hydrothermal liquefaction (HTL) pointed to the generation of an aqueous effluent rich in organic matter of high aromaticity, denominated post hydrothermal wastewater (PHWW). The anaerobic digestion of PHWW was investigated as a treatment option and was evaluated for its energy recovery potential through methane production. Sequencing batch reactors were subjected to increasing initial chemical oxygen demand (COD) levels from 1000 mg COD L−1 to 8000 mg COD L−1, to allow for gradual biomass adaptation to the substrate recalcitrance and toxicity. The highest COD removal rate was observed for an initial COD level of 4000 mg COD L−1. Under this condition, the average methane yield was 187 ± 13 mLCH4 g−1 CODadded, with average COD and total phenols removal efficiencies of 60 ± 1% and 48 ± 4%, respectively. A kinetic evaluation revealed that the methane yield decreased sharply for initial phenolic compounds concentrations above 900 mg GAE L−1. Methane production represented a 22.8% increase in the energy recovered from SCG.
Keywords: Biogas; Crude bio-oil; Inhibition; Polyphenols; Sludge acclimatization